Genetic diversity among early provitamin A quality protein maize inbred lines and the performance of derived hybrids under contrasting nitrogen environments - Obeng-Bio, E.; Badu-Apraku, Baffour; Ifie, B.E.; Danquah, A.; Blay, E.T.; Dadzie, M.A.; Noudifoulè, G.T.; Talabi, A.O. (Springer, 2020)
Information on population structure and genetic diversity of germplasm in a breeding programme is useful because it enhances judicious utilisation of genetic resources to achieve breeding objectives. Seventy early maturing provitamin A (PVA) quality protein maize (QPM) inbreds developed by the IITA- maize improvement programme were genotyped using 8171 DArTseq markers. Furthermore, 96 hybrids derived from 24 selected inbreds plus four checks were evaluated under low-N and optimal environments in Nigeria during 2016 and 2017. Genotypic and phenotypic data of inbreds and hybrids respectively, were analysed to (i) assess the level of genetic dissimilarities and population structure of the inbreds, and (ii) investigate the grain yield performance of derived hybrids under low-N, optimal and across environments.